(3YdGL GNJdGd JhGRf GdYbO GdfGLe Yf GdJYGbO HGSJNOGe GdhSGFW GdMOjKI (B/ s - (3eMeO CMeO YHO GdYRjRs; (3MSf YHOGdHGSW LejYi (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B-(3LGeYI GdbGgQI,s, 2018)
(3JfGhdJ GdOQGSI HYfhGf (B"(3YdGL GNJdGd JhGRf GdYbO GdfGLe Yf GdJYGbO HGSJNOGe GdhSGFW GdMOjKI(B" (3h bGe GdHGMK HGSJNOGe GdefgL GdGSJbQGFi ef NdGd GdGWdGY h bQGAI eLehYI ef GdcJH h GdOQGSGJ GdSGHbI ai eLGd GdYbO GdbGfhfi h cjajI GSJNOGe GdhSGFW GdMOjKI ai YdGL GNJdGd JhGRf GdYbO Yf GSJNOGegG(B: (3h bGe GdHGMK HJbSje GdOQGSI Edi aUd JegjOi HYfhGf (B"(3GdhSGFW GdMOjKI h GdJYGbO Yf HYO(B": (3Ke HGHjf(B: (3GdHGH GdChd HYfhGf (B"(3CHYGO JhGRf GdYbO GdeHQe HGdWQb GdJbdjOjI(B": (3h JfGhd ajg KdGKI aUhd(B: (3h cGf YfhGf GdaUd GdChd (B"(3UhQ GNJdGd JhGRf GdYbO GdeHQe HGdWQb GdJbdjOjI(B": (3CeG GdaUd GdKGfi (B"(3GdCMcGe GdYGeI dJhGRf GdYbO ai GdbGfhf GdeOfi(B" (3h GdaUd GdKGdK (B"(3GdVeGfGJ GdJTQjYjI dJhGRf GdYbO GdJbdjOi(B": (3CeG GdHGH GdKGfi acGf HYfhGf (B"(3GdhSGFW GdMOjKI hJhGRf GdYbO(B": (3h Je JbSje Edi KdGKI aUhd(B: (3acGf GdaUd GdChd (B"(3CKQ GdJYGbO HGdhSGFW GdMOjKI Ydi JhGRf GdYbO(B": (3h GdaUd GdKGfi (B"(3Cge UhQ GdGNJdGd ai JhGRf GdYbO GdeHQe YHQ GdhSGFW GdMOjKI(B" (3h GdaUd GdKGdK (B"(3VeGfGJ JhGRf GdYbO GdEdcJQhfi(B": (3h CNJJe GdHGMK GdOQGSI HNGJeI eNJUI deG JhUd Edjg GdHMK(B: (3Ke bGFeI GdeQGLY GdJi GYJeO YdjgG GdHGMK ai EYOGO gPg GdOQGSIs
(3agQS(B: (3UaMGJ (B367-370.s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdeOfj (B2018. s
(3HHdjhLQGajG(B: (3UaMGJ (B354-366.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdYbOs; (3GdYbO GdEdcJQhfjs; (3JhGRf GdYbOs; (3GdGNJdGd ai GdJhGRf GdYbOi s; (3GdJYGbO Yf HYO s; (3GdhSGFW GdeOfjI s; (3GdCMcGe GdYGeIs; (3GdhSGFW GdMOjKIs; (3QSGFd LGeYjI s -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs